2022
DOI: 10.1111/jch.14550
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and right ventricular function: A meta‐analysis of speckle tracking echocardiographic studies

Abstract: The authors investigated the association between obstructive sleep apnea (OSA) and right ventricular (RV) systolic dysfunction trough a meta-analysis of echocardiographic studies providing data on RV mechanics as assessed by longitudinal strain (LS).A systematic search was conducted using PubMed, OVID-MEDLINE, and Cochrane library databases to search English-language review papers published from inception to March 31, 2022. Only studies reporting data on RV free-wall or global LS in patients with OSA of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In a study with 42 conscious healthy dogs, global longitudinal strain and strain rate showed a correlation with breed and weight ( 55 ). In humans, the estimation of right ventricular mechanics remains challenging due to the complex right ventricular shape and retrosternal location in the mediastinum, which complicates echocardiographic assessment of the right ventricular ( 56 , 57 ). Similarly, in veterinary echocardiography, this is further complicated by various thoracic shapes present in different breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 42 conscious healthy dogs, global longitudinal strain and strain rate showed a correlation with breed and weight ( 55 ). In humans, the estimation of right ventricular mechanics remains challenging due to the complex right ventricular shape and retrosternal location in the mediastinum, which complicates echocardiographic assessment of the right ventricular ( 56 , 57 ). Similarly, in veterinary echocardiography, this is further complicated by various thoracic shapes present in different breeds.…”
Section: Discussionmentioning
confidence: 99%
“…RV global and free-wall longitudinal strains represent parameters of RV systolic function and mechanics, which provide more information than conventional parameters (TAPSE, FAC, s’, and myocardial performance index) due to their higher sensitivity, specificity, reproducibility, and predictive value in a large spectrum of cardiovascular conditions [ 7 , 8 , 9 ]. Table 2 summarizes data about RV GLS and free-wall RVLS at baseline and strain values, as well as RV systolic parameters after CPAP therapy.…”
Section: Mechanisms Of Rv Remodeling In Osamentioning
confidence: 99%
“…Our meta-analysis that included almost all aforementioned studies showed significantly lower RV GLS and free-wall RVLS in OSA patients compared with controls, as well as in patients with severe OSA in comparison to those with mild OSA [ 8 ]. The meta-regression analysis showed a significant association between AHI and RV GLS in all included OSA patients [ 8 ]. It should be also noted that TAPSE was reduced in OSA patients included in this meta-analysis, but it was not able to differentiate mild from moderate or severe OSA.…”
Section: Mechanisms Of Rv Remodeling In Osamentioning
confidence: 99%
See 2 more Smart Citations